Anxiety and rumination moderate menstrual cycle effects on mood in daily life - Welz, Annett; Kühner, Christine (Women & health, 2016)
Evidence for menstrual cycle-related mood fluctuations in the general population of women has been mixed. While most previous research has relied on retrospective self-report and did not consider possible moderators, the present study aimed to examine cycle-related mood variations in daily life and possible moderating effects of anxiety and trait rumination. Fifty-nine women with natural menstrual cycles, aged 18-44 years, were examined between January and October, 2012. Mood components of calmness, positive valence, energetic-arousal, and irritability were assessed, using smartphones, by ambulatory assessment ten times per day on eight days across the cycle. The menstrual, follicular, ovulatory, and late luteal phases were each covered by two consecutive assessment days. Moderators were assessed with questionnaires. Hierarchical linear models (HLMs) revealed higher calmness in the luteal and menstrual than in the follicular and ovulatory phase, while the menstrual cycle did not exhibit significant main effects on other mood components. Anxiety and ruminative self-reflection moderated the association between menstrual cycle and all mood variables. Specifically, highly anxious and ruminative women showed an increase in irritability, while women with lower anxiety and lower rumination were protected against mood deterioration toward the end of the cycle. Further research could examine whether reducing anxiety and rumination helps to prevent premenstrual syndrome-related syndromes.